In the Aftermath of Act 10: The Changed State of Teaching in a Changed State. Issue 4 (8th August 2017) - Swalwell, Katy; Schweber, Simone; Sinclair, Kristin; Gallagher, Jennifer; Schirmer, Eleni
Abstract : Act 10, the 2011 legislative ruling in Wisconsin that reduced public-sector unions' collective bargaining power, provides a descriptive case study to examine what happens to teachers when collective bargaining disappears. Analysis of interviews with social studies teachers ( n = 26) from a stratified random sample of 13 districts shows that the most salient changes for teachers post-Act 10 include increased workloads, reduced pay and benefits, decreased job stability, and unchecked school board and administrative power. These findings are consistent across communities of different sizes and political leanings. In concert with a slew of other reforms initiated within a context of decreased union power, these changes have led to teachers feeling uncertain and vulnerable as well as experiencing a loss of "meaningful teaching." Interviewees expressed doubts about whether they should continue teaching and concerns for the future of the profession.